Nematodoses of pigs in The Republic of Crimea and morphometric parameters of helminth eggs - A. A. Pasechnik; G. A. Lukyanova; N. V. Volozhaninova (Аграрная наука Евро-Северо-Востока)
Analysis of prevalence of nematosis in pigs in the Republic of Crimea is done. Research materials in technological slaughter animals have shown that in the intestine there are parasitic nematodes of four types (Ascaris, Trichuris, Metastrongylus, Strongylata) in the form of monoinvazion and in various combinations. Struck pigs intestinal nematodes was 54.24 %. Invasion of Trihuris suis was biggest among intestinal helminth infections of pigs (22.87%), of Ascaris suum infestation was 20.26%, Strongylata - 9.15%, Metastrongylus - 1.96%. Morphometric parameters of helminth eggs at different degrees of infestation intensity in mono- and mixed forms of helminthiasis were established in the program ImageJ (Wayne Rasband of Research Services Branch of the National Institute of Mental Health). During the studies it was noted that by increasing the intensity of infection the size of helminth eggs reduced: length by 1.05 times and the width by 1.04 times at Trichuris; 1.04 times - Ascaris length and 1.02 times - their width. For Strongylus eggs it is characterized a significant reduction in morphometric parameters: length by 1.83 times, the width - by 1.71 times. At a mixed invasion (Ascaris and Metastrongylus) it is revealed an antagonistic relationship, which manifest themselves in the form of increased morphometric parameters of eggs of Ascaris suum: length by 1.02 times, the width - by 1.07 times. Dimensions of eggs of Trichuris were reduced at mixed invasion with Ascaris suum (length by 1.06 times, width by 1.02), indicating the expression of partial antagonism. The data on the spread of nematodes in pigs in the territory of the Crimean peninsula and morphometric parameters of helminth eggs are important for therapeutic and preventive measures aimed at the elimination of helminth infections, and can also be used for diagnostic examinations of pigs.